2023
DOI: 10.3390/foods12102066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effects of Spray Drying Conditions on Physicochemical Properties of Pomegranate Juice Powder Enriched with Pomegranate Peel Phenolic Compounds: Modeling and Optimization by RSM

Jouhaina Hadree,
Fakhri Shahidi,
Mohebbat Mohebbi
et al.

Abstract: In this study, the effects of pomegranate peel extract concentration (2.5–10%), drying temperature (160–190 °C), and feed flow rate (0.6–1 mL/s) on the properties of pomegranate juice powder enriched with pomegranate peel phenolic compounds and produced by spray drying were investigated. The moisture content, water activity (aw), solubility, water absorption capacity (WAC), hygroscopicity, dissolution time, total phenolic content (TPC), Carr index (CI), Hausner ratio (HR), and brightness (L*) of the samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…11th Edition, all the obtained powders meet the criteria of dried extracts since their MC values were below 5% [32]. Hadree et al [33] analysed pomegranate powder enriched with the phenolic extract of PP by spray drying with an MC between 7.84% and 11.39%, which was two-to-three-fold higher than in the powders obtained in this research.…”
Section: Moisture Content (Mc)mentioning
confidence: 75%
“…11th Edition, all the obtained powders meet the criteria of dried extracts since their MC values were below 5% [32]. Hadree et al [33] analysed pomegranate powder enriched with the phenolic extract of PP by spray drying with an MC between 7.84% and 11.39%, which was two-to-three-fold higher than in the powders obtained in this research.…”
Section: Moisture Content (Mc)mentioning
confidence: 75%
“…PSO is a population-based meta-heuristic optimization algorithm motivated by the cooperative behavior of foraging animals such as flocks of birds or schools of fish. , Multiple linear regression (MLR) is a statistical analysis method used in machine learning. Few studies are using these methods for juice optimization. The combination of RSM, MLR, and PSO can provide more accurate results in component optimization in vegetable juices. When the literature was scanned, no studies were found investigating the optimization of parsley juice’s chlorophyll and ascorbic acid components with RSM, MLR, and PSO after ultrasound application.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies are using these methods for juice optimization. 21 25 The combination of RSM, MLR, and PSO can provide more accurate results in component optimization in vegetable juices. When the literature was scanned, no studies were found investigating the optimization of parsley juice’s chlorophyll and ascorbic acid components with RSM, MLR, and PSO after ultrasound application.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound technology can shorten processing time, extend shelf life, and improve food quality There are a few studies on ultrasound-treated beverages in the literature review. Response surface methodology (RSM) is a collection of valuable statistical methods for process improvement, maintenance, and design. RSM determines the interaction between independent variables and dependent variables. , The use of RSM in beverage optimization has been the focus of many recent studies. …”
Section: Introductionmentioning
confidence: 99%